Multiple tree-ring parameters from Pinus nigra (Arnold) and their climate signal - Poljanšek, Simon (Zbornik gozdarstva in lesarstva, 2012)
The first exploration of climate signal in tree-rings of Black pine (P. nigra Arnold), using minimum blue intensity method, is presented. Sampled trees were growing on site Kojnik (Slovenia). For resin extraction and scanning, 5 mm thick cores were prepared. Whole tree-ring widths were measured, as well as the width and density of early- and latewood. To remove age trend and influence of non-climatic factors, raw measurements were standardized using spline function. In density measurements, highly significant correlation values were calculated between May-June summed precipitation and earlywood density (r = 0.64, p<0.001), while maximum latewood density correlates the best with mean June-August temperature (r = 0.42, p<0.01). In width measurements, the highest correlation was calculated between tree-ring width and mean June-August temperature (r = -0.62, p<0.001).
Keywords: branike; črni bor; klimatski signal; Kojnik; metoda odboja modrega spektra; Pinus nigra; suša